2017
DOI: 10.3389/fphar.2017.00142
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression Changes in the Transcriptome of the Prefrontal Cortex after Repeated Exposure to Cocaine in Mice

Abstract: Prefrontal cortex (PFC)-dependent functions, such as executive function, explicit learning, and memory, are negatively affected in cocaine abusers and experimental animal models of cocaine treatment. However, its molecular mechanisms are less understood. In the present study, we performed transcriptome profiling of the dynamic changes in the PFC after repeated cocaine administration in mice. We found 463, 14, and 535 differentially expressed genes (DEGs) at 2 h, 24 h, and 7 days, respectively, after the withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Recent evidence shows histone lysine demethylase, KDM6B, is significantly increased during cocaine withdrawal in the mPFC (Li et al , 2017; Sadakierska-Chudy et al , 2017); however, the mechanisms involved in this change are unknown. KDM6B, also known as one of the JmjC domain-containing proteins (JMJD3), catalyzes the removal of methyl marks from histone 3 at lysine 27 (H3K27).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows histone lysine demethylase, KDM6B, is significantly increased during cocaine withdrawal in the mPFC (Li et al , 2017; Sadakierska-Chudy et al , 2017); however, the mechanisms involved in this change are unknown. KDM6B, also known as one of the JmjC domain-containing proteins (JMJD3), catalyzes the removal of methyl marks from histone 3 at lysine 27 (H3K27).…”
Section: Introductionmentioning
confidence: 99%
“…RNASeq studies can provide an overwhelming amount of transcriptomic data; however, integrating the results from different studies has been difficult. For example, RNASeq analyses performed 2 hours, 24 hours, and 7 days after cocaine exposure yielded profoundly different results [72]. Differences in the depth of sequencing analysis and the completeness of the reporting of the sequencing data have made comparisons even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies report RNASeq data for the nucleus accumbens, striatum, or prefrontal cortex of mice [13, 19, 23, 26, 72–75] or monkeys [76]; however, not all had been treated with psychostimulants. The number of differentially expressed transcripts varied widely, with 4513 identified in cocaine-treated mice [74] and 328 identified in monkeys [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK signaling cascade involves the activation of extracellular signal-regulated kinases-1 and -2 (ERK1 and ERK2) and is known to play an important role in the control of synaptic plasticity in the adult brain ( Thomas and Huganir, 2004 ). In fact, MAPK/ERK signaling contributes to various behavioral effects of cocaine, such as psychomotor sensitization, conditioned place preference, and reconsolidation of memories for cocaine cues ( Lu et al, 2004 , 2005 , 2006 ) ( Radwanska et al, 2005 ). Our previous study also demonstrated that cocaine treatment induced long-lasting changes of the ERK signaling pathway in the PFC ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%